Testing and referral patterns in the years surrounding the US Preventive Services Task Force recommendation against prostate‐specific antigen screening. Issue 24 (22nd September 2016) - Hutchinson, Ryan; Akhtar, Abdulhadi; Haridas, Justin; Bhat, Deepa; Roehrborn, Claus; Lotan, Yair
Abstract : BACKGROUND: Since the US Preventive Services Task Force (USPSTF) recommended against prostate‐specific antigen (PSA) screening, there have been conflicting reports regarding the impact on the behavior of providers. This study analyzed real‐world data on PSA ordering and referral practices in the years surrounding the recommendation. METHODS: A whole‐institution sample of entered PSA orders and urology referrals was obtained from the electronic medical record. The study was performed at a tertiary referral center with a catchment in the southern United States. PSA examinations were defined as screening when they were ordered by providers with appointments in internal medicine, family medicine, or general internal medicine. Linear and quadratic regression analyses were performed, and joinpoint regression was used to assess for trend inflection points. RESULTS: Between January 2010 and July 2015, there were 275, 784 unique ambulatory visits for men. There were 63, 722 raw PSA orders, and 54, 684 were evaluable. Primary care providers ordered 17, 315 PSA tests and 858 urology referrals. The number of PSA tests per ambulatory visit, the number of referrals per ambulatory visit, the age at the time of the urology referral, and the proportion of PSA tests performed outside the recommended age range did not significantly change. The PSA value at the time of referral increased significantly ( P = .022). Joinpoint analysis revealed no joinpoints in the analysis of total PSA orders, screening PSA tests, or examinations per 100 visits. CONCLUSIONS: In the years surrounding the USPSTF recommendation, PSA behavior did not change significantly. Patients were referred at progressively higher average PSA levels. The implications for prostate cancer outcomes from these trends warrant further research into provider variables associated with actual PSA utilization. Cancer 2016;122:3785–3793. © 2016 American Cancer Society. Abstract : In a whole‐institution sample of prostate‐specific antigen ordering, researchers at the University of Texas Southwestern Medical Center have found no change in overall prostate‐specific antigen ordering, but patients are being referred to urology providers at significantly higher average prostate‐specific antigen values. The implications for prostate cancer outcomes from these trends warrant further research into provider variables associated with actual PSA utilization. See also pages 3760‐1.